1993
DOI: 10.1083/jcb.121.6.1221
|View full text |Cite
|
Sign up to set email alerts
|

GLUT-4 NH2 terminus contains a phenylalanine-based targeting motif that regulates intracellular sequestration.

Abstract: Abstract. Expression of chimeras, composed of portions of two different glucose transporter isoforms (GLUT-1 and GLUT-4), in CHO cells had indicated that the cytoplasmic NH: terminus of GLUT-4 contains important targeting information that mediates intracellular sequestration of this isoform (Piper, R. C., C. Tai, J. W. Slot, C. S. Hahn, C. M. Rice, H. Huang, D. E. James. 1992. J. Cell Biol. 117:729-743). In the present studies, the amino acid constituents of the GLUT-4 NH2-terminal targeting domain have been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
115
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(123 citation statements)
references
References 47 publications
7
115
1
Order By: Relevance
“…Our data now suggest that the N-terminal domain of full-length GLUT4 possesses a critical internalisation motif. This motif is likely to be the phenylalanine-based (FQQI) sequence which is important for GLUT4 sequestration in CHO cells [25] and 3T3-L1 cells [27]. However, we cannot completely exclude the possibility that N-terminal GFP also sterically hinders the C-terminal dileucine motif; however, this is rather unlikely in view of the fact that GFP placed at the Cterminus of GLUT4 does not hinder internalisation.…”
Section: Gfp-glut4mentioning
confidence: 65%
See 2 more Smart Citations
“…Our data now suggest that the N-terminal domain of full-length GLUT4 possesses a critical internalisation motif. This motif is likely to be the phenylalanine-based (FQQI) sequence which is important for GLUT4 sequestration in CHO cells [25] and 3T3-L1 cells [27]. However, we cannot completely exclude the possibility that N-terminal GFP also sterically hinders the C-terminal dileucine motif; however, this is rather unlikely in view of the fact that GFP placed at the Cterminus of GLUT4 does not hinder internalisation.…”
Section: Gfp-glut4mentioning
confidence: 65%
“…Previous studies have concluded that GLUT4 possesses at least two signals that may be responsible for targeting the transporter to this intracellular location in fibroblasts. One, a phenylalanine-based (FQQI) motif, is close to the N-terminus [25,27] and the other, a dileucine motif, is found in the Cterminal tail [29,30]; however, other motifs may be involved [13]. Mutagenesis of either motif causes GLUT4 to be targeted to the plasma membrane of cells (reviewed in [3]).…”
Section: Gfp-glut4mentioning
confidence: 99%
See 1 more Smart Citation
“…This recycling apparently occurs via the clathrin-coated pit pathway as GLUT4 labelling of cell-surface clathrin-coated pits and lattices has been observed in both non-stimulated and insulin-stimulated adipocytes [10]. It is also not surprising that an investigation of the targeting motifs that regulate the intracellular sequestration of GLUT4 has revealed motifs, one in the N-terminus [39] and one in the C-terminus [40], that appear to modulate internalization from the cell surface.…”
Section: Glut4 Is Localized To Recycling Endosomesmentioning
confidence: 99%
“…According to the currently accepted translocation model, originally proposed by Cushman and Wardzala [5] and Suzuki and Kono [6], insulin evokes a redistribution of both GLUT4 and GLUT1 from the interior of the cell to the plasma membrane, but the increased capacity of the cell to transport glucose is due mainly to GLUT4. Studies using chimaeric GLUT1-GLUT4 proteins expressed in both insulin-sensitive and insulinunresponsive cell models in a transient or stable manner helped to identify structural motifs among the transporter molecules responsible for their differential sorting within the cell [7][8][9][10][11]. Thus both the N-and C-termini of GLUT4 contain sequence information responsible for sequestering the transporter into the cell interior, but to different subcompartments ; the insulinsensitive endosomal compartment recognizes the C-terminal 30 amino acids of GLUT4 [11].…”
Section: Introductionmentioning
confidence: 99%